2011
DOI: 10.1002/adsc.201100013
|View full text |Cite
|
Sign up to set email alerts
|

Phenols and Tertiary Amines: An Amazingly Simple Hydrogen‐Bonding Organocatalytic System Promoting Ring Opening Polymerization

Abstract: International audienceA simple and easily available organocatalytic system was developed for the polymerization of lactide. In partnership with tertiary amines, phenol derivatives were demonstrated to be excellent single H-bonding catalysts with high conversion within 24 h. In particular, ortho-, meta- and meta,meta'-trifluoromethylphenols revealed an amazing capacity for triggering the controlled ring opening polymerization (ROP) of lactide, through a fitted hydrogen-bond with the monomer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 34 publications
1
46
1
Order By: Relevance
“…7,[20][21][22][23][24]26 In addition, the bifunctional catalytic system possessing two activation sites for the monomer and propagating chain end also turned out to be effective for the ROP of ε-caprolactone (ε-CL) and LA. [27][28][29][30][31][32][33][34][35][36][37] For example, 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as a bifunctional catalytic system promotes the ROP of the ε-CL, whereas DBU is ineffective, 20 and the MSA/DMAP bifunctional 4 catalytic system promotes the ROP of the LA, whereas MSA alone does not work. 31 Despite such numerous efforts, there are still many problems to be overcome for the industrial scale production of aliphatic polyesters using an organocatalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…7,[20][21][22][23][24]26 In addition, the bifunctional catalytic system possessing two activation sites for the monomer and propagating chain end also turned out to be effective for the ROP of ε-caprolactone (ε-CL) and LA. [27][28][29][30][31][32][33][34][35][36][37] For example, 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as a bifunctional catalytic system promotes the ROP of the ε-CL, whereas DBU is ineffective, 20 and the MSA/DMAP bifunctional 4 catalytic system promotes the ROP of the LA, whereas MSA alone does not work. 31 Despite such numerous efforts, there are still many problems to be overcome for the industrial scale production of aliphatic polyesters using an organocatalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst 2MP had a lower rate constant than phenol. This was not surprising as previous theoretical calculations showed that an intramolecular hydrogen bond is formed between the OH and o‐OMe substituent . Nonetheless, 2MP enhanced the reaction rate as compared to an uncatalyzed reaction.…”
Section: Resultsmentioning
confidence: 55%
“…Crosslinking and gelation was previously observed at elevated temperatures for fatty acid based 6CC monomers . Given the potential for ROP and crosslinking when using TBD, DBU, and TU, we also surveyed a range of weaker alcohol‐based hydrogen bond donors whose catalytic activity can be tuned via structural modifications …”
Section: Resultsmentioning
confidence: 99%
“…Instruments NMR Spectra were recorded in CDCl 3 or C 6 D 6 on BRUKER Avance 300, 400, and 500 MHz spectrometers at room temperature and chemical shifts are reported in ppm relative to Me 4 Si as an external standard. 1 H measurements were used to determine the monomer conversion, the NMR degree of polymerization (DP NMR ), and the end group fidelity.…”
Section: Methodsmentioning
confidence: 99%
“…Various H-bond donor moieties with one, two or three binding sites have been used. 1b The most common are thioureas, 2 perfluorinated alcohols, 3 phenols, 4 squaramides, 5 sulfonamides, 6 amido-indoles.…”
mentioning
confidence: 99%